Local Plastic-Eating Bacteria: The Key to Bioremediation in Indonesian Coastal Waters - Kun Mardiwati Rahayu; Yuli Hardina (Science Journal Get Press, 2026)
Marine plastic pollution is a critical environmental problem in Indonesian coastal waters, where inadequate waste management and high population density contribute substantially to plastic leakage into the marine environment. Indigenous plastic-degrading bacteria offer a potentially low-cost bioremediation strategy, yet locally isolated strains remain poorly characterized. This study aimed to isolate, screen, and molecularly identify indigenous bacteria capable of degrading polyethylene terephthalate (PET) and low-density polyethylene (LDPE) from seawater, sediment, and plastic-debris samples collected at three stations in Bungus Bay, Padang City, West Sumatra. From 42 morphologically distinct colonies, five isolates with the largest clear zones were selected and identified through 16S rRNA gene sequencing as strains related to Bacillus cereus, Pseudomonas aeruginosa, Rhodococcus ruber, Achromobacter xylosoxidans, and Bacillus subtilis. Quantitative degradation assays conducted in triplicate over 90 days showed that a three-isolate consortium achieved the highest weight loss of PET (16.3%) and LDPE (11.2%), significantly exceeding single-isolate treatments and abiotic controls (ANOVA, Duncan’s test, p < 0.05). FTIR analysis confirmed polymer oxidation, with carbonyl indices increasing from 0.18 to 0.34 for PET and from 0.05 to 0.21 for LDPE. These findings demonstrate considerable biodegradation potential under laboratory conditions, although field validation is required before in-situ application for marine bioremediation purposes.